The role of developing management decisions process and structuring investment projects analysis in ensuring the sustainability of various types of companies - D. A. Borisyuk; O. E. Astafyeva (Управление)
During the restart of the investment cycle in the new economic reality, the Government of the Russian Federation has adopted and is preparing to implement a number of measures designed to simplify the implementation of investment projects and thereby create prerequisites for maintaining interest in investing in the real sector of the economy. Thanks to the current model of financial support for investment projects in Russia, a diverse and necessary toolkit is available to the investor when choosing ways to make investments in order to make management decisions on the implementation of projects aimed at ensuring the sustainability of companies of various types. Naturally, within the framework of preparing management decisions for the implementation of investment projects, the question arises of rationally determining the parameters of financial support for an investment project, taking into account all aspects of its implementation, from the choice of sources of financing to the procedure for returning capital raised, as well as structuring projects when assessing their compliance with ESG (Environmental, Social, Governance) criteria. The purpose of this work is to study the importance of structuring an investment project in ensuring the sustainability of companies, to study all aspects of project implementation as part of the management decision-making process, which directly affects the possibility of its implementation. The methodological and theoretical basis of the article is general scientific and particular scientific approaches devoted to the issues of structuring projects in the framework of preparing investment decisions. In addition, CyberLeninka, eLibrary.Ru, Scopus, Web of Science, and Google Scholar were used as academic databases. To ensure the accuracy of the literature review process, all publications were independently reviewed by the authors. An analysis of the procedure for preparing and making investment decisions, structuring projects was made. The authors’ logic of interpreting the goal of structuring in making managerial decisions on project financing is proposed.